Sidewall Aneurysm Geometry as a Predictor of Rupture Risk Due to Associated Abnormal Hemodynamics - Wan, Hailin; Ge, Liang; Huang, Lei; Jiang, Yeqing; Leng, Xiaochang; Feng, Xiaoyuan; Xiang, Jianping; Zhang, Xiaolong (Frontiers in Neurology, 2019)
BACKGROUND Hemodynamics play an important role in intracranial aneurysm (IA) initiation, growth and rupture. Yet there remains no definitive quantitative analysis between abnormal hemodynamics and geometrical risk of IA development. OBJECTIVE The present study aims to investigate whether abnormal hemodynamics in IA sacs can indeed rely upon surrogate geometric markers. METHODS Computational fluid dynamics (CFD) simulations were performed on paraclinoid aneurysm derived from digital subtraction angiography of 104 IAs in 104 patients. Geometries of IA sac, maximum height, perpendicular height, maximum width and neck diameter were measured. Abnormal hemodynamics were defined and quantified as the surface area exposed to low wall shear stress (WSS) and high oscillatory shear index (OSI) using objectively-defined thresholds. Relationships between abnormal hemodynamics and various geometric parameters were analyzed via multiple linear regression. RESULTS Adjusting for age, sex and other clinical characteristics, multiple linear regression revealed a significant relationship (p < 0.001) between abnormal hemodynamics and both maximum width (β ≈ 1.2) and neck diameter (β ≈ -0.4), but not maximum height or perpendicular height. These findings were shown to be independent of the choice of abnormal hemodynamic indicators and threshold levels. CONCLUSIONS Maximum width and neck diameter of IA sacs are robust surrogates of exposure to abnormal hemodynamics. IAs with large maximum width and small neck diameter may be prone to rupture.